2002
DOI: 10.1159/000048173
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Phenotype in Children Is Associated with Decreased Virus-Induced Interferon-α Release

Abstract: Background: Interferon-α (IFN-α) production in humans is an early event in the nonspecific cellular response to viruses and mediates a wide range of antiviral and immunoregulatory activities. Little is known about the role of IFN-α in allergic disease. Methods: In the present study, we performed a retrospective comparative analysis of 88 children with and without an atopic phenotype for virus-induced IFN-α production in blood cultures. Results: We were able to demonstrate that patients with allergic asthma (aA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 28 publications
7
87
1
Order By: Relevance
“…Several groups of investigators have reported that cultured cells from adults and children with asthma synthesise less type I and type III IFN in response to in vitro infection with live viruses [7][8][9][10]. Our study adds to these earlier studies by highlighting abnormal TLR7 function in asthma, implying that an impaired response to viral ssRNA (the natural ligand for TLR7) may contribute to impaired anti-viral innate immunity in this disease.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Several groups of investigators have reported that cultured cells from adults and children with asthma synthesise less type I and type III IFN in response to in vitro infection with live viruses [7][8][9][10]. Our study adds to these earlier studies by highlighting abnormal TLR7 function in asthma, implying that an impaired response to viral ssRNA (the natural ligand for TLR7) may contribute to impaired anti-viral innate immunity in this disease.…”
Section: Discussionsupporting
confidence: 53%
“…When cultured bronchial epithelial cells are infected with RV, cells from asthmatic subjects produce less interferon (IFN)-b and IFN-l relative to healthy donors [7,8]. Alveolar macrophages and circulating leukocytes from asthmatics also appear to have a deficient capacity to synthesise type I and type III IFN [7,9,10], suggesting that the impaired anti-viral response in asthma involves not just structural cells of the lung, but also migratory immune cells and their precursors within the circulation. However, the molecular mechanisms leading to altered anti-viral innate immunity in asthma are not clear.…”
mentioning
confidence: 99%
“…In support of a common underlying predisposition, low IFN-g responses during early life have been associated with greater risk of early childhood wheeze and allergy (12)(13)(14). Furthermore, impaired innate immune responses have been associated with allergy and asthma (15,16). However, our data regarding the directionality of the observed relationship between allergic sensitization and HRV-wheezing illness demonstrate that the former is significantly more likely to precede the development of the latter.…”
Section: Discussionmentioning
confidence: 51%
“…RV-stimulated alveolar macrophages from asthmatics produce less IFN-l than alveolar macrophages from healthy individuals (7). PBMC from asthmatic children and adults secrete less IFN-a following in vitro exposure to viruses (11,12), and this is associated with reduced function of TLR7, the receptor for viral ssRNA (13). Plasmacytoid dendritic cells (pDC) are a potent source of type-I IFN synthesis during virus infections (14), and numerical changes in circulating pDC have been linked both to asthma development in young children (15) and to established asthma in adults (16).…”
mentioning
confidence: 99%